1991
DOI: 10.1104/pp.95.4.1113
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Deficiency in Maize

Abstract: Maize (Zea mays L.) is a betaine-accumulating species, but certain maize genotypes lack betaine almost completely; a single recessive gene has been implicated as the cause of this deficiency (D Rhodes, PJ Rich [1988] Plant Physiol 88: 102-108). This study was undertaken to determine whether betaine deficiency in diverse maize germplasm is conditioned by the same genetic locus, and to define the biochemical lesion(s) involved. Complementation tests indicated that all 13 deficient genotypes tested shared a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 19 publications
(36 reference statements)
2
30
0
Order By: Relevance
“…The levels of free Cho accumulated by PEAMT ϩ transgenics are well above normal ranges for plant tissues, where the ceiling is Ϸ1 mol g Ϫ1 FW (25)(26)(27). However, these free Cho levels are below those that can accumulate in plant tissues supplied with Cho, as are the phosphocholine levels (15,28).…”
Section: Peamt Overexpression Depletes Ea and Phosphoethanolamine Poolsmentioning
confidence: 99%
“…The levels of free Cho accumulated by PEAMT ϩ transgenics are well above normal ranges for plant tissues, where the ceiling is Ϸ1 mol g Ϫ1 FW (25)(26)(27). However, these free Cho levels are below those that can accumulate in plant tissues supplied with Cho, as are the phosphocholine levels (15,28).…”
Section: Peamt Overexpression Depletes Ea and Phosphoethanolamine Poolsmentioning
confidence: 99%
“…Therefore, the inability of rice plants to accumulate glycinebetaine can be probably ascribed in part to a deficiency in the choline oxidation step. The CMO gene in the rice g e n o m e might be either absent or silent (as in maize glycinebetaine deficient lines (Lerma et al, 1991)). If this is the case, then introduction of the CMO gene into rice plants m a y enable t h e m to accumulate glycinebetaine and i m p r o v e salt tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…In others (barley, wheat, rye and certain maize varieties), it runs up to about 10 limol/g fresh weight (Hanson, 1980;Ishitani et aL, 1993;Lerma et aL, 1991;Rathinasabapathi etaL, 1993). Rice is especially salt-sensitive, mainly at the stage of young seedlings (Flowers and Yeo, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of BADH results in increase of tolerance of salt and osmotic stresses in many organisms [21][22][23]. Using Agrobacterium tumefaciens strain LBA4404 carrying a binary vector pBin438 and a leaf regeneration system, Jia et al [20] demonstrated that overexpression of the BADH gene cloned from Atriplex hortensis in a salt-sensitive to *Address correspondence to these authors at the Institute of Turfgrass Science, Beijing Forestry University, Beijing 100083, China; Tel: 010-919-684-6507; Fax: 010-919-668-0795; E-mail: hanliebao@163.com Institute for Genome Sciences and Policy, Duke University, Durham 27708, USA; Tel: +86-10-6233-7982; Fax: +86-10-6232-2089; E-mail: wei.tang@duke.edu mato cultivar, Bailichun, improved salt tolerance.…”
Section: Introductionmentioning
confidence: 99%